Trouble-shooting deployment and recovery options for various stationary passive acoustic monitoring devices in both shallow- and deep-water applications - Dudzinksi, K.; Brown, S.; Lammers, M.; Lucke, Klaus; Mann, D.; Simard, P.; Wall, C.; Rasmussen, M.; Magnúsdóttir, E.; Tougaard, J.; Eriksen, N. (American Institute of Physics, 2011)
Deployment of any type of measuring device into the ocean, whether to shallow or deeper depths, isaccompanied by the hope that this equipment and associated data will be recovered. The ocean isharsh on gear. Salt water corrodes. Currents, tides, surge, storms, and winds collaborate to increasethe severity of the conditions that monitoring devices will endure. All ocean-related research hasencountered the situations described in this paper. In collating the details of various deployment andrecovery scenarios related to stationary passive acoustic monitoring use in the ocean, it is the intentof this paper to share trouble-shooting successes and failures to guide future work with this gear tomonitor marine mammal, fish, and ambient (biologic and anthropogenic) sounds in the ocean—inboth coastal and open waters.